URGENSI UPAYA PAKSA DALAM PELAKSANAAN PUTUSAN PENGADILAN TATA USAHA NEGARA - Uwaisyah Rani; Gusliana Hb; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The weakness of administrative decision assesed in absence of forceful measures imposed on the defendant administrative. With law No.9 of 2004 and changed with law No.51 of 2009, known forceful measures in administrative decision. Article 116, paragraph 4 „in case the defendant is not willing to implement the binding court decision, to official concerned shall attempt a forced measures such as forced payment of money forced and/or administrative sanction‟. But until now the implementation of rules and technical instruction how both intstrument such a forceful measures implemented has not been issued by the government and by the supreme court. The purpose of this writing is to find out the urgency of forceful measures in the implementation of the binding administrative court decision. Conclusions are (1) many administrative court decision that can not be excecuted, due the factors, both in self respect of defendant and the ansence of the institution of measures. (2) forceful measures as mandated in article 166can be implemented effectively because there‟s no implementing reguletion.(3) theimplementation of forceful measures as a feature of the general principle of good governance, the rule of law. And sanction as a weapon for defendant to implement the administrative court decision.The author suggestion that examined of the problems are, first there should be forcibly implementing regulations regarding it self as the publication of government regulations. Second, confirm the dranft plan of administrative law. Third, indispensable participations of defendant in the execution of administrative court decision to determine the development of execution.Key word : Urgency – forceful measures –administrative court